Estudio de Factibilidad para la Implementación de un Sistema Informático para los Procesos Internos en el CONADIS de la Ciudad de Babahoyo - Carriel Campuzano, Erlyng Fernando (2018)
The daily life of people living with disabilities is not very simple, since many cases the world is not yet designed for people with special needs should, but measures are being taken and policies that within cities have adapters are being taken for wheelchairs, putting ramps for the passage of people with disabilities, sounding traffic lights and among many other aspects, what could be the most difficult: is that almost nothing is being done in relation to introducing people with disabilities to technological world of computers. The need of people with disabilities to be included in the technological world, the learning of computer uses of how to use computer programs for a good development, is a necessity for many years. Therefore, technology and information technology have to start to be accessible to all people regardless of their disability status, as well as computer equipment such as mouse, keyboard, etc., must be restructured, virtual spaces and the network must follow the same course, the first raisins to improve the conditions of disabled people were given by the United States in the late 1980s, but it was only in the early 1990s that the information program Windows 95 maintained options that allowed the use of the system even a small group of disabilities. Little by little, many more people have contributed with contributions and advances regarding the issue of bringing technology to people with disabilities. to the point that nowadays, there are many programs and tools for people for people with special abilities but the problem lies in the fact that only this is seen in developed countries.